2016
DOI: 10.1016/j.ecoleng.2016.05.076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of straw and polyacrylamide on the stability of land/water ecotone soil and the field implementation

Abstract: Poor stability of land/water ecotone (L/WE) soil is a serious and increasing problem in the context of ecological restoration. Effective management by adding straw and polyacrylamide (PAM), i.e., SPAM, to soil may increase soil stability, including structure and fertility. Thus, it is important to explore the effects of SPAM on L/WE soil, as well as to determine the appropriate ratio of straw and PAM to achieve optimal increases. To investigate the soil properties and provide basis for ecological restoration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The other reason was likely associated with the linear water‐soluble polymer with large molecular weight of PAM (Thombare et al, ). The structure of PAM is able to promote binding and adhesion or flocculation of soil particles (Lu et al, ), leading to the improved soil physical structure in the incorporation layer. Meanwhile, reduced soil mechanical impedance and enhanced aeration through decrease in SBD enhanced the SWS capacity, which potentially reduced water loss out of the rooting zone to the ground water (Laboski, Dowdy, Allmaras, & Lamb, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other reason was likely associated with the linear water‐soluble polymer with large molecular weight of PAM (Thombare et al, ). The structure of PAM is able to promote binding and adhesion or flocculation of soil particles (Lu et al, ), leading to the improved soil physical structure in the incorporation layer. Meanwhile, reduced soil mechanical impedance and enhanced aeration through decrease in SBD enhanced the SWS capacity, which potentially reduced water loss out of the rooting zone to the ground water (Laboski, Dowdy, Allmaras, & Lamb, ).…”
Section: Discussionmentioning
confidence: 99%
“…Polyacrylamide (PAM) is a synthetic polymer with a superhigh water retention capacity. It has been used as a soil amendment on construction sites and on millions of hectares of furrow irrigation lands worldwide to improve soil water‐holding capacity and stabilize soil structure, thus decreasing soil degradation and erosion (Entry, Sojka, & Hicks, ; Lu et al, ; Roshanizarmehri et al, ). It is also beneficial in reducing the runoff and nutrient loss (e.g., phosphates and nitrates), maintaining their availability to the crop plants (Entry, Sojka, Watwood, & Ross, ; Lentz, Sojka, & Robbins, ).…”
Section: Introductionmentioning
confidence: 99%
“…As another agricultural waste, straws are rich in cellulose, hemicellulose, lignin and other carbon compounds [ 16 ]; straw production in China accounts for ~25% of the world’s total straw resource [ 17 ] and straw incorporation is considered a potential approach to improve soil fertility and even boost rice production [ 18 , 19 , 20 ]. Previous studies found that straw return could improve soil organic matter (SOM) and structural stability during degradation processes, leading to a better soil function [ 21 , 22 , 23 ]. Moreover, several studies showed that straw addition could increase the activities of soil enzymes, including urease, phosphatase and catalase [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the application of polyacrylamide (PAM) reduces the loss of soil NH 4 + and NO 3 - (Li & Wang, 2016) and facilitates microbial growth and metabolism (Li et al, 2013), and the application of humic acid improves soil agglomerate structure and enhances the absorption of nitrogen by crops (Vlcková et al, 2009), increasing grain yield and total biomass (Pamela et al, 2014). However, at present, the polymer materials used in many studies are solids (Awad et al, 2012;Lu et al, 2016;Luo et al, 2015), and several researches on liquid polymer materials are only carried out in potted plants by spraying (Li & Wang, 2016;Wang et al, 2011). Therefore, in this study, three polymer materials were used to analyse their effects on the transformation and utilization of soil nitrogen combined with drip irrigation.…”
Section: Introductionmentioning
confidence: 99%